Intravenous Ondansetron Efficacy in Preventing Post Spinal Shivering during Lower Segment Caesarean Section - Komail Abid; Rashid Iqbal; Syed Ali Raza Shah; Sana Tariq (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine IV Ondansetron efficacy in preventing post-spinal shivering during LSCS.